Cytotoxicity evaluation, antibacterial effect, and degree of conversion of QAM-containing adhesives - Isadora Martini GARCIA; Tatiana Féres ASSAD-LOSS; Luis Felipe Jochinms SCHNEIDER; Fabrício Mezzomo COLLARES; Larissa Maria Assad CAVALCANTE; Mônica Almeida TOSTES (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to evaluate the influence of adding quaternary ammonium methacrylates (QAMs) to experimental adhesives by assessing the degree of conversion (DC), cytotoxicity against keratinocytes and fibroblasts, and antibacterial activity against biofilm formation. Two QAMs were added to an experimental adhesive: dimethylaminododecyl methacrylate bromododecane (DMADDM) or dimethylaminododecyl methacrylate bromohexadecane (DMAHDM) at three concentrations each: 1, 2.5, and 5 wt.%. Experimental adhesive without QAMs (control group) and commercially available Transbond XT Primer (3M Unitek, Monrovia, California, USA) were used for comparisons. The adhesives were tested for DC, cytotoxicity against keratinocytes and fibroblasts, and antibacterial activity against biofilm formation. DC, cytotoxicity against fibroblasts, and antibacterial activity were analyzed using one-way ANOVA and Tukey's multiple comparisons. Cytotoxicity against keratinocytes was evaluated using the Kruskal Wallis and Dunn's post-hoc (α = 5%) tests. Transbond showed lower DC as compared to 5% DMAHDM, 1% DMADDM, and 5% DMADDM (p < 0.05). However, all groups presented proper DC when compared to commercial adhesives in the literature. In the evaluation of cytotoxicity against keratinocytes, Transbond induced higher viability than 2.5 wt.% groups (p < 0.05). Against fibroblasts, Transbond induced higher viability as compared to 5 wt.% groups (p < 0.05). DMAHDM at 5 wt.% reduced biofilm formation when compared to all the other groups (p < 0.05). Despite their cytotoxic effect against keratinocytes, gingival fibroblasts showed higher viability. DMAHDM at 5 wt.% decreased Streptococcus mutans viability. The incorporation of DMAHDM at 5 wt.% may be a strategy for reducing the development of white spot lesions.